A broadband P2P MoD system: its implementation and application. (26th May 2009) - Liu, Shyh-Chang; Chen, Tsung-Hung; Wang, Peng-Shiang
This paper studies the scalable query process under Multimedia on Demand (MoD) system, and characters its data and queries its workloads. For the current system, our study shows poor performance in interaction and trans-media. The solutions we develop based on the Peer-to-Peer (P2P) MoD system and provide a new framework in which to tackle business model. The business model we present shares contents by integrated P2P technique and Sharable Content Object Reference Model (SCORM) concepts, and Cosine R-Tree data structure for system loading, content features clustering, contents redirection and user queries. Experiments validate the potential benefits of the new platform.